Faktor yang Berhubungan dengan Tingkat Pengetahuan Masyarakat dalam Mengelola Obat Sisa, Obat Rusak dan Obat Kedaluarsa - Hananditia Rachma Pramestutie; Ratna Kurnia lllahi; Ayuk Lawuningtyas Hariadini; Tamara Gusti Ebtavanny; Tia Eka Aprilia (Faculty of Pharmacy, Universitas Gadjah Mada)
Problems that often arose as a result of improper management of unused, damaged, and expired drugs in storage and disposal, include drug abused, increased environmental damage, antibiotic resistance, and decrease effectiveness of therapy; due to the lack of public knowledge that can caused by several factors. This study aims to analyse factor associated with level knowledge in the management of unused, damaged, and expired drugs in Malang Raya. This study was an observational analytic study with a cross-sectional design. The subjects were the people of Malang Raya who were selected using a convenience sampling technique in accordance with the inclusion and exclusion criteria. The subjects were 322 respondents. The instrument used was a questionnaire to measure the level of knowledge of respondents that had been tested for validity and reliability. The results showed that, level of knowledge of respondence at Malang Raya in the management of unused, damage and expired drugs in the good (21%), sufficient (58%), and less (21%). Statistical tests used in this study were Somers'd, Kruskal-wallis, and Lambda tests to analysed factor associated with subjects’ level of knowledge in the management of unused, damaged, and expired drugs. There were a significant relationship in factors included age (p = 0.018) and income level (p = 0.003). It can be concluded that among the factors associated with the level of knowledge in the management of unused, damaged, and expired drugs, only age and income level were statistically significant. Further study is needed to determine the factors affecting the level of knowledge the most.